2017
DOI: 10.1002/hec.3554
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional performance assessment of public sector organisations using dominance criteria

Abstract: Public sector organisations pursue multiple objectives and serve a number of stakeholders. But stakeholders are rarely explicit about the valuations they attach to different objectives, nor are these valuations likely to be identical. This complicates the assessment of their performance because no single set of weights can be chosen legitimately to aggregate outputs into unidimensional composite scores. We propose the use of dominance criteria in a multidimensional performance assessment framework to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 78 publications
0
23
0
1
Order By: Relevance
“…Both increasing average age and the associated prevalence of multiple chronic conditions in contemporary patient populations can complicate the assessment of healthcare management, so that methods that can accommodate multi-dimensional outcomes would be useful. However, we are aware of only one study that has provided a strategy to rank providers in a multi-dimensional setting, by proposing a dominance criterion [5]. Thus, methods for assessing multiple healthcare outcomes are required.…”
Section: Introductionmentioning
confidence: 99%
“…Both increasing average age and the associated prevalence of multiple chronic conditions in contemporary patient populations can complicate the assessment of healthcare management, so that methods that can accommodate multi-dimensional outcomes would be useful. However, we are aware of only one study that has provided a strategy to rank providers in a multi-dimensional setting, by proposing a dominance criterion [5]. Thus, methods for assessing multiple healthcare outcomes are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, no diagnostic information is presented from the principal component analysis to support the assumption of unidimensionality and the use of a single principal component. In other studies, quality indicators have been shown to be multidimensional . Based on their analysis, Lieberthal and Comer concluded that
patient satisfaction is a poor measure of quality….
…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, quality indicators have been shown to be multidimensional. [18][19][20][21][22] Based on their analysis, Lieberthal and Comer concluded that patient satisfaction is a poor measure of quality…. the best hospitals were not the ones that were the quietest or that had the most responsive clinicians.…”
mentioning
confidence: 99%
“…Given the challenge of finding suitable instrumental variables, we avoid the causal identification problem and motivated by the methodology used in studies that have assessed performance in physical health care [22,23], we analyse costs and outcomes using two separate equations and allow for a correlation in responses. As in previous studies [14,21] we measure quality in terms of an outcome measurethe Health of the Nation Outcome Scale (HoNOS).…”
Section: Introductionmentioning
confidence: 99%
“…As in previous studies [14,21] we measure quality in terms of an outcome measurethe Health of the Nation Outcome Scale (HoNOS). Following earlier studies [18,[21][22][23] we use multi-level modelling which allows us to examine the correlation in residual responses at provider-level to provide insight into the relationship between costs and outcomes and whether a potential trade-off exists.…”
Section: Introductionmentioning
confidence: 99%